The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.2196/jmir.1728
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Personal Side of Health: How Patient Expertise Differs from the Expertise of Clinicians

Abstract: BackgroundWhen patients need health information to manage their personal health, they turn to both health professionals and other patients. Yet, we know little about how the information exchanged among patients (ie, patient expertise) contrasts with the information offered by health professionals (ie, clinician expertise). Understanding how patients’ experiential expertise contrasts with the medical expertise of health professionals is necessary to inform the design of peer-support tools that meet patients’ ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 53 publications
(68 reference statements)
7
148
0
2
Order By: Relevance
“…Oliveira et al (2015) found that 36% of all patients with a chronic condition or their relatives innovated in relation to their needs. These findings are in line with a growing body of literature that indicates that patients are gaining increased medical expertise in relation to their disease (Budych et al 2012;Hartzler and Pratt 2011;Greenhalgh 2009;Thorne et al 2000).…”
Section: Discussionsupporting
confidence: 87%
“…Oliveira et al (2015) found that 36% of all patients with a chronic condition or their relatives innovated in relation to their needs. These findings are in line with a growing body of literature that indicates that patients are gaining increased medical expertise in relation to their disease (Budych et al 2012;Hartzler and Pratt 2011;Greenhalgh 2009;Thorne et al 2000).…”
Section: Discussionsupporting
confidence: 87%
“…Tensions due to perceived incompatibility between expertise types and sources can be experienced as cognitive inconsistency (Monge and Contractor 2003), leading consumers to question the legitimacy (Tost 2011) of clinical expertise, especially when compared with their experiential lay expertise (Hartzler and Pratt 2011).…”
Section: Structural Tension 3: Managing a Fragmented And Complex Servmentioning
confidence: 99%
“…Personal health informatics systems for tracking one's personal health variables have been attributed to promoting self-reflection and awareness in self-care (Aarhus et al 2009). Online health communities and forums have been shown to empower patients to learn from each other (Hartzler and Pratt 2011) and provide social-emotional support to patients who may not be able to obtain such support in their offline relationships (Preece 1998). Similarly, Internet-based social networks have been promoted as an effective way for patients to gain emotional support and help from family and friends (Skeels et al 2010;Pols 2012).…”
Section: Introductionmentioning
confidence: 99%